Penggunaan Media Papan Pintar untuk Meningkatkan Hasil Belajar Siswa Kelas 3 pada Materi Bilangan Cacah di SDN 1 Babakan - Afifah, Risa Zanuba; Nurhabibah, Prabawati (Indo-MathEdu Intellectuals Journal, 2024)
This research was motivated by the low learning outcomes of Mathematics in addition and subtraction materials in grade 3B students at SDN 1 Babakan. This shows that the Minimum Completeness Criteria (KKM) set by the school, which is 70, has not been achieved. The purpose of this study is to determine the improvement of Mathematics learning outcomes of addition and subtraction materials using smart board learning media. This study uses the Classroom Action Research (PTK) method based on the theory developed by Kemmis and McTaggart which includes the process of planning, action, observation, and reflection. The research was carried out in class 3B of SDN 1 Babakan, Sumber District, Cirebon Regency with a total of 29 students (14 women and 15 boys). Data collection techniques are carried out through observation and tests. Data analysis was carried out descriptively on all research data. The results of the study show that student learning outcomes in learning have improved. In the first cycle, student learning outcomes reached 62% and in the second cycle, student learning outcomes reached 83%. The conclusion that can be drawn from this study is that the use of Smart Board Media can improve student learning outcomes in Mathematics learning in grade III of SDN 1 Babakan